Protected Agricultural Production of Vegetables. Implementing protected agriculture in tomato, bell peppers, and colored chili peppers - Gutiérrez Montenegro, Jaime Martín; Benavidez Fuentes, Santiago; Valdivia Lorente, Rodolfo Ramón (Catholic Relief Services, 2015)
This publication is the product of a participatory capitalization process facilitated by the International Center for Tropical Agriculture (CIAT) for the Program for Rural Enterprise Management, Health, and the Environment (PROGRESA). This document aims to share the results of an initiative of PROGRESA that addressed the implementation of farming systems based on macroand mega-tunnels to produce vegetables for both selective and local markets.